1994
DOI: 10.2172/10105917
|View full text |Cite
|
Sign up to set email alerts
|

Summary of California DSM impact evaluation studies

Abstract: Portions of this document may be illegible in electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…There is no single reason to explain the discrepancy between the pre-program estimates and our savings estimates, based on actual billing data. This difference, however, is very consistent with the findings from numerous other evaluations that examined pre-program estimates (Brown and Mihlmester 1994). We have reviewed the pre-program analysis (see Lee et al 1995) and find that several factors might contribute to the difference between those results and ours.…”
Section: Comparison With Other Resultssupporting
confidence: 87%
“…There is no single reason to explain the discrepancy between the pre-program estimates and our savings estimates, based on actual billing data. This difference, however, is very consistent with the findings from numerous other evaluations that examined pre-program estimates (Brown and Mihlmester 1994). We have reviewed the pre-program analysis (see Lee et al 1995) and find that several factors might contribute to the difference between those results and ours.…”
Section: Comparison With Other Resultssupporting
confidence: 87%
“…Some of the programs offered direct assistance (measures are installed at no cost to the customer) and some shared savings incentives (where both the utility and the customer invest in measures and share the benefits of reduced bills). Brown and Mihlmester (1994) found that the lowest realization rates were in residential direct assistance programs ( w i t h a mean of 68% and a median of 53%). The realization rates for commercial, industrial, and agricultural programs were higher than residential realization rates, and the shared incentive programs had higher realization rates than the direct assistance programs.…”
Section: Previous Research On Audit Realization Ratesmentioning
confidence: 98%
“…Another study of realization rates in the Demand-Side Management programs of the four largest California utilities summarized the results of over 50 evaluation studies of programs operating between 1990 and 1992 (Brown and Mihlmester, 1994). The programs reviewed included efforts in several end-use sectors (including commercial, industrial, agricultural and residential).…”
Section: Previous Research On Audit Realization Ratesmentioning
confidence: 99%